2000
DOI: 10.1002/(sici)1097-4644(20000201)76:2<217::aid-jcb6>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Effects of static or dynamic mechanical stresses on osteoblast phenotype expression in three-dimensional contractile collagen gels

Abstract: Studies performed at tissular (three-dimensional, 3-D) or cellular (two-dimensional, 2-D) levels showed that the loading pattern plays a crucial role in the osteoblastic physiology. In this study, we attempted to investigate the response of a 3-D osteoblastic culture submitted to either no external stress or static or dynamic stresses. Rat osteosarcoma cells (ROS 17/2.8) were embedded within collagen type I lattices and studied for 3 weeks. Entrapment and proliferation of cells within the hydrated collagen gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…[21] In addition, the mechanical strength of hydrogels has been reported to affect the growth and function of enclosed mammalian cells. [22,23] Figure 3 shows stress/strain profiles of CMC-Ph gels prepared from 1.0 and 2.0 wt.-% solutions of CMC-Ph8 and CMC-Ph15. The stress/strain profiles of the gels were similar before rupture of the CMCPh15 gel.…”
Section: Gel Strengthmentioning
confidence: 99%
“…[21] In addition, the mechanical strength of hydrogels has been reported to affect the growth and function of enclosed mammalian cells. [22,23] Figure 3 shows stress/strain profiles of CMC-Ph gels prepared from 1.0 and 2.0 wt.-% solutions of CMC-Ph8 and CMC-Ph15. The stress/strain profiles of the gels were similar before rupture of the CMCPh15 gel.…”
Section: Gel Strengthmentioning
confidence: 99%
“…Recent studies have showed that collagen fibril morphology is critically important in determining the tensile strength of the associated tissues and, thus, provides a scaffold for the cell adhesion [5,6]. Some experimental data showed that the collagen morphological structures could affect the adhering, growth and differentiation of a variety of cells in cell culture applications [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…While static loading conditions facilitate experimental investigation, the natural physiological environment is dynamic and changes with time. In fact, studies have demonstrated that many cell types respond differently depending on whether a given mechanical stimulus (e.g., stretch, flow) is applied in a static or dynamic manner (1,4,12,14,36,40,44,46,58). For instance, while static deformation causes a reduction in chondrocyte biosynthetic activities, dynamic deformational loading results in an upregulation of chondrocyte biosynthetic activity (6,49).…”
mentioning
confidence: 99%